EFEKTIVITAS PENGGUNAAN MODUL IPA DALAM PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 PADA SISWA KELAS VIII MTsN 2 KOTA KEDIRI - Krismayanti, Yuly Rizki; Sudibyo, Elok (PENSA E-JURNAL: PENDIDIKAN SAINS, 2021)
This study aims to determine the effectiveness of the science module developed by the Directorate of Junior High Schools in distance learning during the Covid-19 pandemic. The subjects of this study were students of class VIII-D and VIII-E MTsN 2 Kediri. The number of students in class VIII-D was 31 students and class VIII-E was 32 students. The method used in this research is a research method pre-experimental with a one-shot case study design. Data collection techniques used in this study were tests and questionnaires. The data analysis technique used in this research is descriptive quantitative. The effectiveness of the developed modules in terms of the percentage of classical completeness, students ’learning completeness seen from the indicators of competency achievement, and students’ responses related to the developed modules. The instruments used were test sheets and questionnaire sheets. The results obtained in this study are that the developed module is effective in terms of the percentage of classical completeness of 83.87% for class VIII-D and 84.37% for class VIII-E. Completeness based on the competency achievement indicators, students succeeded in achieving 5 indicators of competency achievement from the total number of 6 indicators of competency achievement indicators, and the students’ responses were very good. The conclusion of this study is that the module developed by the Directorate of Junior High Schools was effectively applied to distance learning during the Covid-19 pandemic as a medium for independent learning.